Is Xbox 360 Kinect-based virtual reality training as effective as standard physiotherapy in patients undergoing breast cancer surgery? - Feyzioğlu, Özlem; Dinçer, Selvi; Alkan, Arzu; Algun, Zeliha Candan (Springer, 2020)
Purpose: Breast cancer surgery may be associated with pain and physical symptoms in the upper limbs. Functional impairment and pain-related avoidance of movement may further increase disability level. This study aimed to investigate the potential effects of early postoperative virtual reality (VR) therapy on pain, range of motion (ROM), muscle strength, functionality, and fear of movement. Methods: Forty women with breast cancer who had undergone unilateral mastectomy with axillary lymph node dissection and who were receiving adjuvant therapy were included in the study and randomly assigned to two groups: the Kinect-based rehabilitation group (KBRG) and the standardized physical therapy group (SPTG). The KBRG (n = 20) received VR therapy using Xbox Kinect-based games and the SPTG (n = 20) received standard physiotherapy. Study subjects were assessed at baseline and after the 6-week treatment. Outcome measures were pain (visual analogue scale), grip strength (dynamometer), functionality (disabilities of the arm shoulder and hand questionnaire), muscle strength (handheld dynamometer), ROM (digital goniometer), and fear of movement (Tampa kinesiophobia scale (TKS)). Results: Both groups detected significant changes in pain, ROM, muscle strength, grip strength, functionality, and TKS scores after the treatment (p < 0.01). Fear of movement was significantly improved in the KBRG and the SPTG displayed more improvement in functionality (p < 0.05). There were no differences in ROM, muscle strength, grip strength, and pain between the groups after the treatment (p > 0.05). Conclusion: Kinect-based VR therapy resulted in significant outcomes that were comparable to those obtained under standard physiotherapy in the early postoperative phase in patients who had undergone breast cancer surgery. Trial registration: This study is registered at ClinicalTrials.gov (ClinicalTrials.gov identifier: NCT03618433).
Keywords: Breast Cancer; Xbox Kinect; Virtual Reality; Physical Therapy; Video Games